New developments in difference equations and applications : proceedings of the Third International Conference on Difference Equations, Taipei, Republic of China, September 1-5, 1997 /: proceedings of the Third International Conference on Difference Equations, Taipei, Republic of China, September 1-5, 1997. (2017) - Unknown
No abstract available